Borderlands of the identity: cultural duality and native american identity in Leslie Marmon Silko`s "Ceremony" - Fondo, Blossom N. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Cultural displacement constitutes one of the main features of colonial encounters. This is due to the different control mechanisms employed by the forces of colonialism to subjugate the dominated groups. This paper looks at one of the consequences of this cultural displacement which is the condition of in-betweenness in Leslie Marmon Silko`s novel "Ceremony".
Keywords: identity; cultural duality; white hegemony; in-betweenness; Native Americans